The ameliorative effects of various fish protein hydrolysates in poultry by-product meal based diets on muscle quality, serum biochemistry and immunity in juvenile barramundi, Lates calcarifer. Issue 104 (September 2020) - Chaklader, Md Reaz; Fotedar, Ravi; Howieson, Janet; Siddik, Muhammad A.B.; Foysal, Md Javed
Abstract: In an effort to reduce the use of fishmeal (FM), the effect of using protein from poultry by product meal (PBM) along with the supplementation of three different fish protein hydrolysate (FPH) including yellowtail kingfish, carp and tuna hydrolysate (designated as KH, CH and TH, respectively) were evaluated in juvenile barramundi for growth performance, fillet quality, mucosal immunity, serum biochemistry, immune response and infection against Vibrio harveyi . Fish were fed a FM based control diet + three isonitrogenous and isolipidic diets containing 90% of PBM protein supplemented with different types of hydrolysates: 90% PBM +10% KH (90PBM + KH), 90% PBM + 10% CH (90PBM + CH) and 90% PBM + 10% TH (90PBM + TH). Growth performance and indices were unaffected by the hydrolysate supplemented diets when compared to the control. FPH supplemented PBM diets resulted in improved muscle quality by improving poly unsaturated fatty acids (PUFA), ∑n-3, ∑n-6 and ∑n-9, and health related lipid indexes were not affected. The internal architecture of spleen and kidney were not altered by test diets whilst FPH supplemented PBM modulated acidic mucins in intestine and skin of fish. Improved infection rate in response to two weeks post infection with V. harveyi in the FPH supplemented diets was further associated with an increased serum immune response and a concomitant regulation of proinflammatory and inflammatory cytokines in the head kidney. Serum biochemistry including alanine transaminase (ALT), glutamate dehydrogenase (GLDH) and total bilirubin (TB) showed a decreasing trend both in pre-challenge and post-challenge barramundi fed FPH supplemented diets whereas cholesterol level decreased significantly in post-challenge groups fed 90PBM + KH and 90PBM + TH than pre-challenge barramundi. This study signifies that supplementation of 10% with different three FPH, hydrolysed by an alcalase® enzyme in PBM-based diets for barramundi could be good strategies to overcome the negative consequences triggered by animal by-product ingredients. Highlights: Supplementation of 10% of various FPH hampered negative effects caused by PBM. Acidic mucins in intestine and skin were modulated by the supplementation of carp and tuna hydrolysate with PBM. The infection rate in response to Vibrio harveyi decreased in various FPH supplemented PBM groups. Lysozyme activity and immune-relevant genes expression increased in post-challenge groups fed various FPH supplemented PBM.